ANALISIS YURIDIS MEKANISME PENANGANAN TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG UNTUK MEWUJUDKAN PERLINDUNGAN HAK ASASI MANUSIA (STUDI PENELITIAN DIREKTORAT RESERSE KRIMINAL UMUM KEPOLISIAN DAERAH KEPULAUAN RIAU) - Tri Yani Joy Duha; Fadlan Fadlan; Juhrin Pasaribu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In this era, in the era of globalization, we increasingly find crimes that are increasing in the community, one of which is the crime of trafficking in persons.. Trafficking in persons has been agreed upon by the international community as a violation of human rights. The Indonesian government has shown its intention to eradicate these crimes despite the fact that there is the involvement of perpetrators who are mutually organized networks in broad syndicates and even abroad. This study aims to determine the legal arrangements for the way law enforcement treats victims of trafficking crimes and to determine the implementation, constraints and solutions of law enforcement in dealing with trafficking cases at the Directorate of General Criminal Investigation of the Kepri Regional Police. This type of research uses an empirical / sociological type of research using the normative juridical approach method, namely in the form of an analysis of legal arrangements that regulate things that occur problems to obtain secondary data and a sociological juridical approach to obtain primary data through field research. Obstacle factors include services in the context of recovering/rehabilitating victims in health and social aspects and victim repatriation services to the area of origin or proper shelter according to the needs of the victim. The study concluded that: The legal regulation of the Trafficking in Persons Act is considered to be incomplete and universal, the handling of victims of the Trafficking in Persons Act is not only the responsibility of the Police, but is the responsibility of the Government, Community Institutions.It is recommended that the prevention and handling of trafficking crimes must be carried out optimally and integratedly by cooperating with the community and Governments and community institutions in the fight against trafficking in persons.Keywords: Human Trafficking, Human Rights, Investigations